A beleza, o assombro e as paixões: a retórica do projeto arquitetônico de um templo religioso - Sousa, Luciano Andrade de (2021)
The present study aims to verify the application of rhetorical concepts in the celebrative space of a Catholic temple, specifically for the project of the Chapel Nossa Senhora de Lourdes, linked to the parish Santa Rita de Cassia in Franca, state of São Paulo. The goal is due to a gap that we believe exists regarding the rhetorical analysis of Catholic temples. This gap is related to a specific context of the 21st century church, which is: Catholic temples in country cities, built through campaigns and promotions, with the help of parishioners. For the development of this work, we rely on Aristotelian rhetoric, specifically in the works Rhetoric (2005) and Rhetoric of the Passions (2000). We also rely on Michel Meyer's The Rhetoric (2005) and Olivier Reboul's Introduction to Rhetoric (2004). The concepts describing the stages of the argumentative process and the parts of the discourse, presented by Figueiredo and Ferreira (2016), who also worked with authors such as Aristóteles, Perelman, and Olbrechts-Tyteca, Meyer and Reboul, were studied precisely, as well as the concepts of the trajectory of the passions, described in Figueiredo (2020). The analysis took place through different approaches. Initially, we use the concepts linked to the stages of the argumentative process – Inventio, Dispositio, Elocutio, and Actio – to confront them with the projectual path through which the architect passes in the creation of the temple. In turn, the parts of the discourse - Exordium, the Narration, the Confirmation, and the Peroration - were instruments for the analysis of the project to be executed and its elements as a future work. At last, the final project was analyzed under the concepts of the trajectory of passions, specifically as to its three initial stages, namely "availability", "identification" and "awakening of passion". From the latter, the study explains which possible passions can be aroused by means of the constituent elements of the architectural project. Keywords: Architecture; Rhetoric; Religious temple; Trajectory of passions.